Danegaptide Enhances Astrocyte Gap Junctional Coupling and Reduces Ischemic Reperfusion Brain Injury in Mice - Freitas-Andrade, Moises (Biomolecules, 2020)
Ischemic stroke is a complex and devastating event characterized by cell death resulting from a transient or permanent arterial occlusion. Astrocytic connexin43 (Cx43) gap junction (GJ) proteins have been reported to impact neuronal survival in ischemic conditions. Consequently, Cx43 could be a potential target for therapeutic approaches to stroke. We examined the effect of danegaptide (ZP1609), an antiarrhythmic dipeptide that specifically enhances GJ conductance, in two different rodent stroke models. In this study, danegaptide increased astrocytic Cx43 coupling with no significant effects on Cx43 hemichannel activity, in vitro. Using matrix-assisted laser desorption ionization imaging mass spectrometry (MALDI IMS) the presence of danegaptide within brain tissue sections were detected one hour after reperfusion indicating successful transport of the dipeptide across the blood brain barrier. Furthermore, administration of danegaptide in a novel mouse brain ischemia/reperfusion model showed significant decrease in infarct volume. Taken together, this study provides evidence for the therapeutic potential of danegaptide in ischemia/reperfusion stroke.